2010
DOI: 10.1121/1.3483738
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and synchrony differences in auditory brainstem responses evoked by chirps of varying durations

Abstract: The chirp-evoked ABR has been termed a more synchronous response, referring to the fact that rising-frequency chirp stimuli theoretically compensate for temporal dispersions down the basilar membrane. This compensation is made possible by delaying the higher frequency content of the stimulus until the lower frequency traveling waves are closer to the cochlea apex. However, it is not yet clear how sensitive this temporal compensation is to variation in the delay interval. This study analyzed chirp-and click-evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…For the recording of chirp-evoked ABRs, auditory steady-state responses, ASSRs, and post-auricular muscle responses, PAM responses, the ER-2 earphone was used by Dau et al (2000), Wegner and Dau (2002), Fobel and Dau (2004), Elberling and Don (2008), , and Petoe et al (2010b). The ER-2 earphone was also used by Don et al (2005) to record the derived-band ABR-latencies used to formulate the traveling wave model for the chirp designed by Elberling and Don (2008).…”
Section: A Backgroundmentioning
confidence: 99%
“…For the recording of chirp-evoked ABRs, auditory steady-state responses, ASSRs, and post-auricular muscle responses, PAM responses, the ER-2 earphone was used by Dau et al (2000), Wegner and Dau (2002), Fobel and Dau (2004), Elberling and Don (2008), , and Petoe et al (2010b). The ER-2 earphone was also used by Don et al (2005) to record the derived-band ABR-latencies used to formulate the traveling wave model for the chirp designed by Elberling and Don (2008).…”
Section: A Backgroundmentioning
confidence: 99%
“…The auditory brainstem response (ABR), to upward chirp stimuli has previously been studied and described in a number of publications (Dau et al, 2000;Fobel and Dau, 2004;Elberling et al, 2007;Elberling and Don, 2008;Don et al, 2009;Cebulla and Elberling, 2010;Petoe et al, 2010aPetoe et al, , 2010b. As described in the previous paragraph, the upward chirp-or just the chirp-is a brief stimulus which attempts to compensate for the mechanical and neural temporal dispersion in the cochlea.…”
mentioning
confidence: 98%
“…Since frequency-dependent delays are shown by measures that reflect neural synchrony at the level of the AN and brainstem (e.g., Dau et al, 2000;Petoe et al, 2010b), the hypothesized compensating mechanism could be involved in the transmission of information from the brainstem to the midbrain or/and the central nuclei or could be more central in origin. Given the millisecond scale of the phenomenon, however, a brainstem or midbrain locus seems more plausible than a cortical one.…”
Section: Introductionmentioning
confidence: 99%
“…Noninvasive physiological measures of peripheral auditory responses in humans have shown that frequencydependent basilar-membrane (BM) traveling-wave delays result in a progressive delay of low frequencies relative to higher frequencies in the representation of a stimulus transmitted to the auditory nerve (AN) and subsequent processing stages (e.g., Elberling, 1974;Eggermont, 1979;Neely et al, 1988;Schoonhoven et al, 2001;Shera et al, 2002;Sisto and Moleti, 2007;Harte et al, 2009). Auditory brainstem responses (ABRs) to a chirp designed to counteract the frequency-dependent delays and to synchronize the BM responses across locations with different characteristic frequencies (CFs) exhibit a greater amplitude of wave V (Dau et al, 2000;Fobel and Dau, 2004), greater amplitudes of high-frequency (HF) components of the ABR spectrum, and a smaller phase variance of the main ABR components (Petoe et al, 2010b) than the ABRs to a click with the same overall energy. These results suggest that differences in response latencies across CFs introduced by cochlear filtering are preserved at least up to the level of the brainstem.…”
Section: Introductionmentioning
confidence: 99%